2014
DOI: 10.1108/scm-12-2013-0436
|View full text |Cite
|
Sign up to set email alerts
|

Framing sustainability performance of supply chains with multidimensional indicators

Abstract: Purpose – This paper aims to provide a framework which can assist focal companies in the development of sustainable supply chains. Sustainable development from an industrial perspective has extended beyond organisational boundaries to incorporate a supply chain approach. Design/methodology/approach – The literature related to sustainable supply chain management is reviewed by incorporating concepts from four organisational theories, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
194
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(218 citation statements)
references
References 149 publications
2
194
1
5
Order By: Relevance
“…Several contributions in the supply chain literature propose sustainability indicators, metrics or evaluation systems in the environmental and social aspects [9][10][11][12][13][14]47]. Previous literature has identified that mostly environmental and economic performance are considered in sustainable supply chain studies [2,7,28,31], therefore for the aims of this study, we concentrate on the environmental and social dimensions.…”
Section: Research Question 2: Sustainability Performance In the Fscmentioning
confidence: 99%
See 1 more Smart Citation
“…Several contributions in the supply chain literature propose sustainability indicators, metrics or evaluation systems in the environmental and social aspects [9][10][11][12][13][14]47]. Previous literature has identified that mostly environmental and economic performance are considered in sustainable supply chain studies [2,7,28,31], therefore for the aims of this study, we concentrate on the environmental and social dimensions.…”
Section: Research Question 2: Sustainability Performance In the Fscmentioning
confidence: 99%
“…Similarly, regarding social performance, the evaluation areas proposed in literature include ethical behavior, stakeholder engagement, human rights observance and occupational safety. These types of metrics, indicators or measurement areas have been described in general and specifically for the food industry [9,11,12,14,[33][34][35]. For instance, some studies focused on the environmental impact for industries in general [2,23,36], or particularly for food [21,33].…”
Section: Sustainability Performance In the Fscmentioning
confidence: 99%
“…Nonetheless, literature provides a number of supply chain performance measurement methods which can also be used (Torabizadeh, 2014). On the other hand, additional research can be made with the concepts we studied on sustainable supply chain performance (Varsei, 2014 .774…”
Section: Resultsmentioning
confidence: 99%
“…It can make a considerable contribution to both the economic and environmental development. This general perspective has been named green or environmentally sustainable supply chain management (Varsei et al 2014). This new trend has developed more line the Green Supply Chain Management (GSCM) conceptan important approach to becoming environmentally sustainable Yang et al 2013;HooBae et al 2011).…”
Section: Literature Reviewmentioning
confidence: 99%